Keorganisasian PGRI DKI Jakarta dan Perannya dalam Pengelolaan Dana Hibah untuk Guru Swasta Tahun - Rani Noviyanti; Nurbaity Nurbaity (Jurnal Ilmiah Literasi Indonesia, 2026)
This study aims to analyze the organizational structure of PGRI DKI Jakarta and its role in managing grant funds for private school teachers in 2018. The research employs the historical method through four stages: heuristics, source criticism, interpretation, and historiography. Data were collected from policy documents, technical guidelines of the grant program, organizational archives, and academic literature on educational finance management and public financial governance. The findings indicate that PGRI DKI Jakarta played a strategic role as a mediator between the provincial government and private school teachers, as an administrative executor in the data collection and verification process, and as an internal supervisor in the distribution of grant funds. Although the organizational structure supported program implementation, challenges were identified in transparency, reporting systems, and administrative capacity. The grant program contributed positively to improving the welfare of private school teachers, albeit as supplementary income. This study highlights the importance of strengthening accountability and transparency principles in involving professional organizations in public fund management to ensure effective and sustainable educational policy implementation.